Karakteristik Ekstrak Alga Coklat pada Perlakuan Ukuran Partikel dan Lama Ekstraksi Alga Coklat (Sargassum polycystum) sebagai Antibakteri - Prasetya, I Ketut Dio; Suhendra, Lutfi; Ganda Putra, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 1 (2020): MaretDO - 10.24843/JRMA.2020.v08.i01.p06, 2020)
Sargassum polycystum is one group of brown algae (Phaeophyta) which contain fukoidan compounds. Fukoidan is a complex polysaccharide on seaweed cell walls that can enhance immunity by stimulating the production of immune cells. The purposes of this study were to determine the effect of particle size and extraction time of Sargassum polycystum against fukoidan characteristics and get particle size and extraction time which is the best treatment for getting extraction Sargassum polycystum as an antibacterial. This experiment used a randomized block design with particle size treatment and extraction time. Treatment of 40, 60, and 80 mesh particle sizes and extraction lengths of 3, 4 and 5 hours. The results showed the treatment of particle size, extraction time and interactivity affect the characteristics of brown algae extract (Sargassum polycystum) as an antibacterial. 80 mesh particle size treatment and extraction time of 5 hours is the best treatment to produce brown algae extract (Sargassum polycystum) as an antibacterial with characteristic sulfate content of 15.297 mg / L, inhibitory zone in Escherichia coli with a diameter of 10.15 mm and inhibit zone Staphylococcus aureus with a diameter of 9,13 mm. Keywords: Sargassum polycystum, Extraction, Sulphate, Antibacterial